Social support and physical activity among CKD patients in Hospital Usm - Ahmad, Nur Husnina (Universiti Sains Malaysia, 2023)
Social support is a wide construct that describes the social network resources that an individual receives, and it is described as the perception and reality an individual has been cared for, as assistance and support from society. Social support is a component that can increase a person's motivation to engage in physical activity. The objective of this study is to determine social support and physical activity among CKD patients in Hospital USM. A cross-sectional study design was used in this research. Questionnaires were given and collected using the face-to-face method at the CKD Resources Unit and Klinik Pakar Perubatan (KPP). Descriptive statistics were used to describe respondents and identify the level of social support and physical activity of CKD patients in USM Hospital. Pearson Chi-square was used to test the association between variables. The majority of respondents have moderate social support and moderate physical activity. The results show that there is no relationship between social support and physical activity with a coefficient of p<0.05. There is a need to provide exposure to family members of CKD patients in providing them with enough social support as well as increasing the patient's awareness to do physical activity and hold a physical activity program by providing a physical activity guide that suits their health condition.